A Proposed Pedagogical Mobile Application for Learning Sign Language - Abou El-Seoud, Samir; Taj-Eddin, Islam; Nosseir, Ann; El-Sofany, Hosam; Abu Rumman, Nadine (International Journal of Interactive Mobile Technologies (iJIM), 2013)
A handheld device system, such as cellular phone or a PDA, can be used in acquiring Sign Language (SL). The developed system uses graphic applications. The user uses the graphical system to view and to acquire knowledge about sign grammar and syntax based on the local vernacular particular to the country. This paper explores and exploits the possibility of the development of a mobile system to help the deaf and other people to communicate and learn using handheld devices. The pedagogical assessment of the prototype application that uses a recognition-based interface e.g., images and videos, gave evidence that the mobile application is memorable and learnable. Additionally, considering primary and recency effects in the interface design will improve memorability and learnability.